Consistent Observing of Fetal Pulse and Uterus Withdrawals - P.Thirupathinaidu a, S. Roji Marjoriea, Dr. N.Hephzibah Kirubamania (International Journal of Advanced Science and Technology, 2020)
Fetal monitoring during pregnancy time is the most important to save the life of the mother as well as the child. In this paper, we present a device that is used to measure the fetal heart rate during the time of pregnancy. The major component used for this detection is Fetal Digital stethoscope sensor which is to be placed on the abdomen of the pregnant and the signals are processed by the micro-controller used and the accurate fetal heart rate is identified and sent as a text message to the respective mobile phone through the usage of GSM module and also by the usage of EMG sensor the uterus contraction also be simulated as the output on the desktop. This system is very flexible and low cost helps the patient to monitor the fetal heart rate in  home.